1990
DOI: 10.2135/cropsci1990.0011183x003000010041x
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Callus Induction and Green‐Plant Regeneration in Rice Anther Culture

Abstract: Low efficiencies of callus induction and green‐plant regeneration have limited the application of anther culture in breeding programs. This study was conducted to determine the inheritance of callus induction and plant regeneration in rice (Oryza sativa L.) anther culture. Sixteen genotypes derived from a four‐parent diallel mating set of two Japonica cultivars (Taipei 309 and Taipei 177) and two indica cultivars (IR36 and Basmati 370) were evaluated for their callus induction and plant regeneration abilities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 0 publications
5
32
0
1
Order By: Relevance
“…In addition, additive effects accounted for a larger proportion than the dominant effects for callus induction (179.83, mean square for GCA vs. 31.75, mean square for SCA) and for total plant regeneration (1225.73, for GCA vs. 410.37, for SCA). The present results were similar to previous studies that both additive and dominant gene actions contributed to the variation of callus induction and plant regeneration traits in barley (Powell, 1987;Hou et al, 1994), and for rice anther culture (Quimio and Zapata, 1990) .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, additive effects accounted for a larger proportion than the dominant effects for callus induction (179.83, mean square for GCA vs. 31.75, mean square for SCA) and for total plant regeneration (1225.73, for GCA vs. 410.37, for SCA). The present results were similar to previous studies that both additive and dominant gene actions contributed to the variation of callus induction and plant regeneration traits in barley (Powell, 1987;Hou et al, 1994), and for rice anther culture (Quimio and Zapata, 1990) .…”
Section: Resultssupporting
confidence: 93%
“…As indicated by Zhou and Konzak (1992), the percentage of green-plant regeneration from the anther culture of wheat was under the control of nuclear genes and the action of these genes was predominantly additive. Addit ive and dominant effects have also been reported for the anther culture of barley (Dunwell et al, 1987;Powell, 1987 ;Hou et al, 1994) and rice (Quimio and Zapata, 1990) and in vitro callus formation and plant regeneration in alfalfa (Wan et al, 1988) and red clover (Poerba et al, 1997). Recently, several studies on the factors influencing callus induction and plant regeneration in anther culture of sorghum have been reported (Wen et al, 1991;Kumaravadivel and Rangasamy, 1994;Nakamura et al, 1997;Can et' al., 1998).…”
mentioning
confidence: 99%
“…Many authors have reported that considerable variation among genotypes has been identified (Niizeki and Oono 1968;Mukherjee 1973;Oono 1975;Shen et al 1982;Chen 1988;Li 1991). Moreover, previous studies also showed that anther culture capacity in rice was highly heritable and was controlled by nuclear genes (Miah et al 1985;Quimio and Zapata 1990). These results suggested it might be possible to overcome the limitation through genetic recombination, transferring genes controlling anther culturability from high response into poorly responsive lines.…”
Section: Introductionmentioning
confidence: 91%
“…But the technique can be of practical use in breeding only if it can create sufficient numbers of green plants (Quimio and Zapata 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation